Frequency of Vitamin D Deficiency in Patients of Epilepsy on Valproate Sodium - Abdul Ghafoor Magsi, Mujeeb-Ul-Rehman, Mehtab Ali Shahani, Fahim Ahmed Soomro, Shoaib Ahmed, Safdar Hussain Arain, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of vitamin D deficiency in patients of epilepsy on valproate sodium. Study design: Case control study Place and duration of study: Department of Neurology, Chandka Medical College Hospital, Larkana and Khairpur Medical College, Khairpur Mir’s from 1st July 2021 to 31st December 2021. Methodology: One hundred adults were enrolled which were further divided into two groups. Those patients suffering from clinically determined epilepsy (n=50) and treated for epilepsy were placed in group A and were treated with sodium valproate while healthy adults within same age group were placed in group B (n=50). Clinical assessments were made through neurological assessment for epilepsy. A blood of 2cc was withdrawn from group A and B participants and tested for 25(OH) vitamin D levels by and serum sodium valproate (in only group A) using enzyme linked immunosorbent assay. Results: The mean of group A patients was 24.2±3.5 years while of group B was 28.3±1.5 years. The dosage of sodium valproate in mg/d was given as a mean value of 869± 350.9. The mean serum levels of sodium valproate as assessed was found as 79.8 mmol/L. Body Mass Index value showed that obesity was significantly highly common in group a than Group B.A comparison of vitamin D levels between group A and Group B showed that the severe deficiency as well as deficiency of vitamin D was significantly prevalent (56%) in epileptic group such as group A while insufficiency was also higher in the similar group A. Conclusion: There was a high frequency of vitamin D deficiency in patients with epileptic condition and getting treated with sodium valproate.